IMF Staff Papers, Volume 53, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 2006)
Noteworthy among the six papers appearing in this latest issue of the IMF's peer-reviewed journal is another installment in the Special Data Section. Anthony Pellechio and John Cady from the IMF's Statistics Department take a close look at differences in IMF data; how and when they could occur; and what the implications of such differences might be for end-users of the IMF's data.